Politics, Poetics and “the Tragedy of Existence”. The Reception of Młyny Boże [the Mills of God] Novel Series by Kazimierz Truchanowski by the Censorship Bureau - Mojsak, Kajetan (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article analyzes the censorship board’s reception of Kazimierz Truchanowski’s novel cycle The Mills of the God, published between 1961 and 1967. The analysis gives an insight into the interesting process of the growing tolerance – and indifference – of censorship board towards this kind of hermetic, non-epic prose: far from the official cultural course, but at the same time not coming into open conflict with it. Review of censors’ reception of the subsequent parts of Truchanowski’s novel can be seen as a contribution to the history of the so-called “socparnasizm” as well as to the history of the growing pragmatism of the censorship board (and its de-ideologization).